The mode II interlaminar fracture toughness and healing efficiency of repeatable self-healing composite. (October 2022) - Wang, Zhen; Li, Yan; Tu, Haoyun
Graphical abstract: Abstract: Hollow glass fibers containing self-healing resin (SR) and two types of microcapsules (HGFs-Ms) that can repeatedly heal the crack at the same place were manufactured. The repeatable self-healing carbon-epoxy composites (RSH-CFRPs) were made by incorporating the HGFs-Ms and microcapsules containing hardener into the mid-plane. The effects of the diameter and length of HGFs-Ms, the content of SR and the diameter of the microcapsules containing SR inside HGFs-Ms on the mode II interlaminar fracture toughness, 1 st and 2 nd healing efficiencies of the RSH-CFRPs were studied by performing end-notched flexure tests. The optimal combination of the above parameters was obtained which could result in 69.77% improvement in the fracture toughness compared to virgin CFRPs and could accomplish 100% healing efficiency at the same place twice. The toughening and healing mechanisms of the RSH-CFRPs were deeply analyzed, which proved the effectiveness of the self-healing method proposed in this study.